2002
DOI: 10.1074/jbc.m209795200
|View full text |Cite
|
Sign up to set email alerts
|

Nudix Hydrolases That Degrade Dinucleoside and Diphosphoinositol Polyphosphates Also Have 5-Phosphoribosyl 1-Pyrophosphate (PRPP) Pyrophosphatase Activity That Generates the Glycolytic Activator Ribose 1,5-Bisphosphate

Abstract: A total of 17 Nudix hydrolases were tested for their ability to hydrolyze 5-phosphoribosyl 1-pyrophosphate (PRPP). All 11 enzymes that were active toward dinucleoside polyphosphates with 4 or more phosphate groups as substrates were also able to hydrolyze PRPP, whereas the 6 that could not and that have coenzyme A, NDP-sugars, or pyridine nucleotides as preferred substrates did not degrade PRPP. The products of hydrolysis were ribose 1,5-bisphosphate and P i . Active PRPP pyrophosphatases included the diphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…Such an ion appears to be required by the B. bacilliformis Ap 4 A hydrolase (23) and the E. coli ADPribose pyrophosphatase (33). However, the apparent absence of specific interactions in this region is entirely consistent with our recent discovery that this and related dinucleoside polyphosphate hydrolases can bind and hydrolyze 5-phosphoribosyl 1-pyrophosphate (35). In this case the ribose ring would occupy the P 2 ,P 3 site, with binding dependent solely on interactions in the P 1 and P 4 sites, in agreement with the data above.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Such an ion appears to be required by the B. bacilliformis Ap 4 A hydrolase (23) and the E. coli ADPribose pyrophosphatase (33). However, the apparent absence of specific interactions in this region is entirely consistent with our recent discovery that this and related dinucleoside polyphosphate hydrolases can bind and hydrolyze 5-phosphoribosyl 1-pyrophosphate (35). In this case the ribose ring would occupy the P 2 ,P 3 site, with binding dependent solely on interactions in the P 1 and P 4 sites, in agreement with the data above.…”
Section: Discussionsupporting
confidence: 78%
“…Again, this is consistent with the finding that 5-phosphoribosyl 1-pyrophosphate, which lacks a base altogether, is a substrate. Thus, binding of one adenine ring between the Tyr residues is not an essential requirement for catalysis, although it undoubtedly contributes to the higher specificity constant for Ap 4 A compared with 5-phosphoribosyl 1-pyrophosphate (35). Interestingly, in the NMR structure of the lupin Ap 4 A hydrolase complexed with the substrate analogue ATP-MgF x , the adenine ring is not located between the structurally equivalent residues Tyr 77 and Phe 144 , and instead Tyr 77 is suggested to be important for the structural integrity of the enzyme-substrate complex rather than for direct substrate binding (17).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that some proteins with the Nudix motif act on nonnucleotide substrates such as diphosphoinositol polyphosphates (Safrany et al, 1998(Safrany et al, , 1999, 5-phosphoribosyl 1-pyrophosphate (Fisher et al, 2002), and thiamine pyrophosphate (Lawhorn et al, 2004). Therefore, it seems likely that AtNUDXs with no activity toward any substrate tested here would act on nonnucleotide substrates or be inactive following expression in E. coli and/or purification by affinity chromatography.…”
Section: Atnudxs With No Activitymentioning
confidence: 92%
“…The physiologic function of this pathway remains to be established (319). In addition, certain diphosphoryl (Nudix) hydrolases are able to hydrolyze PRPP with the formation of ribosyl 1,5-bisphosphate and P i (320). Finally, a PRPP pyrophosphatase activity has been identified in macrophages exposed to hypoxia (321).…”
Section: Reactions At the Diphosphoryl Moiety Of Prppmentioning
confidence: 99%